Critical Review—Electrochemical Properties of 13 Vitamins: A Critical Review and Assessment. Issue 2 (27th January 2018) - Lovander, Matthew D.; Lyon, Jacob D.; Parr, Daniel L.; Wang, Junnan; Parke, Brenna; Leddy, Johna
Abstract : Review of the literature on the currently recognized, thirteen vitamins yields an overview of the electrochemical properties that include estimates of the formal potentials at physiological pH and identification of the general classes of redox mechanisms. All vitamins are electroactive and map a range of formal potentials E 0 ′ over a 3 V window. The vitamins are grouped as lipid soluble (vitamins A, D, E, and K) and water soluble (B vitamins and vitamin C). Mechanisms are grouped as single electron transfer agents (B3, B7, B2, C, and D), vitamins that can be both oxidized and reduced (B1, B5, B6, B9, and E), and vitamins that undergo two successive, distinct reductions (B12 and K). Vitamin A voltammetry is uniquely complex. Plot of the formal potentials on a potential axis allows assessment of mechanistic paths to vitamin recycling, antioxidant behavior, pH dependence, electrochemical stability in air, acid, and water, electrochemical instability of vitamin pairs, and cooperative interactions between vitamins in medicine. The potential axis is shown as an effective tool for mapping thermodynamically complex interactions. The voltammetry literature for each vitamin is critically assessed.